P-223 Women aged 40 or older and non-male factor have the same reproductive outcome using intracytoplasmic sperm injection (ICSI) or conventional in vitro fertilization (cIVF). (30th June 2022) - Filardi, P; De Martino, E; Chiarello Sosa, J.M; Gomez Peña, M; Papayannis, M; Figueroa, C; Magri, L; Oubiña, A; Horton, M; De Zuñiga, I; Kopcow, L; Sobral, F; et al.
Abstract: Study question: Do women aged 40 or older have the same reproductive outcome using ICSI or cIVF when male factor infertility is not present? Summary answer: Women aged 40 or older with non-male factor partners achieved similar reproductive outcomes either with ICSI or cIVF. What is known already: Although initially proposed to treat couples with severe male factor infertility, ICSI has become the preferred tool to treat patient populations others than initially intended. Many studies and international forums, however, have alerted that its overuse is not free due to its safety, cost and time-consuming concerns. Moreover, it was noted that it does not increase clinical outcomes even in cases of compromised oocyte factor such as poor responder patients or few oocytes retrieved. However, there is still no information regarding its use in the group of patients of advanced reproductive age. Study design, size, duration: Retrospective cohort study including 412 women aged 40 or older with non-male factor infertility performing ICSI or cIVF between May 2015 and October 2017. Participants/materials, setting, methods: Patients underwent ICSI (n = 109) or cIVF (n = 303) according to medical indication. The decision to use ICSI in non-male factor patients was merely operational, with the objective of evaluating oocyte maturity.Those cycles with own oocytes, non-male factor and fresh embryo transfers were included. Semen samples were considered normal following the World Health Organization fifth edition sperm parameters values, and prepared by density gradient selection. Main results and the role of chance: The primary outcome was clinical pregnancy rate. Secondary outcomes included ongoing pregnancy, miscarriage and implantation rates. Statistical significance was denoted by P < 0.05. The mean age of the women were 41.4 in the ICSI group and 41.6 years in the cIVF group, while the mean age for male couple was 43.6 and 41.6 respectively. No differences between ICSI and cIVF groups were observed regarding clinical pregnancy [16.5% (18/109) vs. 20.8% (63/303)], ongoing pregnancy [9.2% (10/109) vs. 7.9% (24/303)], miscarriage [41.2% (7/17) vs. 46, 5% (20/43)], and implantation rates [11.3% (17/151) vs. 9.9% (50/506)]. Limitations, reasons for caution: These results need confirmation with a bigger population size. As with any retrospective study, the potential for residual confounding exists. Wider implications of the findings: These data suggest that ICSI offers no clinical benefit for women aged 40 and older with non-male factor infertility, beyond oocyte maturation classification. Trial registration number: not applicable